NEW APPROACH FOR TECHNOLOGY OF VOLUMETRIC – SUPERFICIAL HARDENING OF GEAR DETAILS OF THE BACK AXLE OF MOBILE MACHINES - A. I. Mihluk (Литьë и металлургия, 2010)
The new approach for technology of volumetric – superficial hardening of gear details of the back axle made of steel lowered harden ability is offered. This approach consisting in formation of intense – hardened condition on all surface of a detail.